A randomised controlled trial of a care home rehabilitation service to reduce long-term institutionalisation for elderly people - Fleming, Sarah A.; Blake, Holly; Gladman, John R.F.; Hart, Elizabeth; Lymbery, Mark; Dewey, Michael E.; McCloughry, Helen; Walker, Marion F.; Miller, Paul (Oxford University Press, 2004)
Objectives: to evaluate the effect of a care home rehabilitation service on institutionalisation, health outcomes and service use.